Be nimble with threat mitigation: lessons learned from the reintroduction of an endangered species. Issue 1 (6th November 2019) - Robinson, Natasha M.; Dexter, Nick; Brewster, Rob; Maple, Dion; MacGregor, Chris; Rose, Karrie; Hall, Jane; Lindenmayer, David B.
Abstract : Reintroductions are increasingly being used to restore species and ecosystems. However, chances of successful establishment are often low. Key to improving success is careful consideration of threats, threat mitigation, monitoring, and subsequent improvement to management. We demonstrate this planning, implementation, and review process using the reintroduction of an endangered mesopredator, the eastern quoll Dasyurus viverrinus, in the first attempt to reestablish it in the wild on mainland Australia. In March 2018, 20 captive‐bred quolls (10 male, 10 female) were released into Booderee National Park and monitored via telemetry, camera, and cage trapping. There were many unknowns and, despite thorough consideration of threats, there were surprising outcomes. Within 3 months, 80% of animals had died; half due to predation, an expected threat. Other threats were unexpected yet, due to good monitoring and responsive management, were quickly detected and effective mitigation implemented. These learnings have been incorporated into revised translocation procedures. One year later, four founder quolls remained and had successfully bred. We highlight lessons applicable to other reintroductions. These are, the importance of: (1) conducting a thorough review of threats and implementing appropriate mitigation; (2) targeted monitoring and responsive management; (3) effective communication, education, and engagement with the local community and stakeholders; and (4) ensuring learnings are disseminated and incorporated into future translocation plans. Threat assessment is an important step in identifying potential reasons for failure. However, actual threats can be realized only via experimentation and monitoring. Applying this knowledge to future reintroduction attempts can increase their chance of success.